Targeting protein-protein interactions for cancer therapy - Anscombe, E (2012)
Protein-protein interactions (PPIs) are key drug targets and recent breakthroughs in this area are providing insight into the types of molecules needed to selectively and potently inhibit a target traditionally seen as untractable. The rules that have been used to design classic substratecompetitive drugs (for example Lipinski's rule of five) may not apply in this new field in the same way. Here I present work performed in three systems that are well-validated drug targets for oncogenesis: the CDK2/cyclin A complex, the PLK1 Polobox domain and MDM2. In each case the site of the protein-protein interaction is defined and understood and the rationale for pharmaceutical intervention is clear. I use these as a model system to evaluate the characteristics of drugs that target protein-protein interaction sites and present work on the development of inhibitors as potential leads for subsequent drug development. In Chapter 1 I introduce the problems, challenges and rewards of PPI drug development; in Chapter 2 I present co-crystal structures of MDM2 with isoindolinone inhibitors; in Chapter 3 I detail attempts to co-crystallise the Plk1 Polobox with inhibitors and screen potential inhibitors; in Chapter 4 I present the results of screening to identify inhibitors of Cyclin A recruitment; and in Chapter 5 I discuss other strategies for inhibition of the CDK2/cyclin A complex, including results with a covalent inhibitor. Through these projects I have been able to demonstrate the wide applicability of the PPI inhibition approach, identify key features of drugs able to inhibit PPIs and contribute to drug design in each system.